Monitoring of killer yeast populations in mixed cultures: influence of incubation temperature of microvinifications samples - Maturano, Yolanda Paola; Nally, María Cristina; Toro, María Eugenia; Castellanos de Figueroa, Lucía Inés; Combina, Mariana; Vazquez, Fabio (2017)
Killer yeasts are frequently used to combat and prevent contamination by wild-type yeasts during wine production and they can even dominate the wine fermentation. Stuck and sluggish fermentations can be caused by an unbalanced ratio of killer to sensitive yeasts in the bioreactor, and therefore it is important to determine the proportion of both populations. The aim of this study was to provide a simple tool to monitor killer yeast populations during controlled mixed microvinifications of killer and sensitive Saccharomyces cerevisiae. Samples were periodically extracted during vinification, seeded on Petri dishes and incubated at 25 and 37 °C; the latter temperature was assayed for possible inactivation of killer toxin production. Colonies developed under the described conditions were randomly transferred to killer phenotype detection medium. Significant differences in the killer/sensitive ratio were observed between both incubation temperatures in all microvinifications. These results suggest that 37 °C seems a better option to determine the biomass of sensitive yeasts, in order to avoid underestimation of sensitive cells in the presence of killer yeasts during fermentations. Incubation at a toxin-inhibiting temperature clearly showed the real ratio of killer to sensitive cells in fermentation systems.